Komunikasi Negosiasi Dream Aviation dengan Lion Air Group untuk Mendapatkan Carter Pesawat Ibadah Umroh - Azzahra, Aliifah Renissa Putri; Wijaksono, Dimas Satrio (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The increasing demand for airplane tickets for Umrah has made Dream Aviation collaborate with Lion Air Group to get charter flights for Umrah. Dream Aviation is one of Dream Tour's business units that specializes in charter flights for Umrah pilgrims departing from several major cities in Indonesia. The purpose of this research is to find out how the negotiation stages of Dream Aviation with Lion Air Group in obtaining airplane charters for Umrah worship. This research uses a descriptive qualitative method. The research data was collected through the interview method with two key informants from Dream Aviation. Based on the results of the research, the negotiation process between Dream Aviation and Lion Air Group to obtain an airplane charter for Umrah involves several stages described by Bill Scott (1993). These stages include exploration, offering, bargaining, settlement, and ratification. Through careful preparation and building a positive negotiation climate, Dream Aviation successfully submitted the first offer with consideration of market prices and field issues submitted to Lion Air Group. After the bargaining process, both parties reached an agreement with Lion Air Group agreeing to provide several seats under Dream Aviation's request. Thus, an agreement was reached with a win-win solution and was outlined in a contract letter valid for one season with the possibility of an extension for the following season.